Advancing Research in Information and Communication Technology: IFIP's Exciting First 60+ Years, Views from the Technical Committees and Working Groups - Goedicke, Michael; Neuhold, Erich; Rannenberg, Kai (IFIP Advances in Information and Communication Technology, 2021)
For 60 years the International Federation for Information Processing (IFIP) has been advancing research in Information and Communication Technology (ICT).This book looks into both past experiences and future perspectives using the core of IFIP's competence, its Technical Committees (TCs) and Working Groups (WGs).